Determinants of suicidal history before assisted versus self-initiated suicide late in life: an observational study (Swiss Medical Weekly, 2023)
BACKGROUND: Older adults are at risk of assisted and self-initiated suicide. The links between prior attempts and assisted suicide in the elderly have not been investigated. Hence, we aimed to investigate and describe the occurrence, timing and determinants of suicide attempts prior to assisted and self-initiated suicide.METHODS: We developed a retrospective study of all assisted and self-initiated suicides among people over 65 years in the canton of Geneva, Switzerland, for a 10-year period (2010–2019). Cases were identified by cross-referencing hospitals’ routinely collected electronic data and a forensic report database. Cases were characterised in terms of sociodemographic factors, mental health disorders, main comorbidities, temporal sequence, methods of injury, medical complications and disclosure rates of previous attempts. The study used descriptive statistics.RESULTS: A total of 26 of 497 (5.2%) and 20 of 149 (13.4%) older adults had made previous attempts before assisted and self-initiated suicide, respectively. More than half of them had made a single attempt, mostly by medication poisoning, sometimes more than 10 years before dying. Individuals who made two attempts were significantly more represented among the assisted suicide decedents. One self-initiated suicide decedent and half of the assisted suicide cases had disclosed that they had considered suicide. Individual characteristics were similar, except for assisted suicide decedents, who were eight years older than self-initiated suicide decedents. Almost all the individuals had mental disorders. Depression, anxiety and chronic pain were particularly prevalent among decedents of assisted suicide. The substantial representation of women in both groups may be an indication of their vulnerability, possibly related to chronic pain and life stressors.CONCLUSIONS: Our results show commonalities between older assisted and self-initiated suicide decedents who made an attempt (s) before suicide. Further research is needed to demonstrate the overlap between the determinants of assisted suicide and other forms of suicidality and to support a suicide prevention strategy applicable to both types of suicide.